A case of dengue fever in a health worker in university of Port-Harcourt teaching hospital - Egboh, Stella-Maris C.; Otike-Odibi, Bolaji I.; Altraide, Dasetima D.; Awopeju, Abimbola T. O. (International Journal of Research in Medical Sciences, 2018)
Dengue fever is a mosquito borne disease which can easily be missed or misdiagnosed in early stages as a result of poor surveillance, similarity with other febrile illness and unavailability of PCR necessary for its diagnosis. We hereby report a 44year old female nurse living around a bushy and swampy environment, who presented to university of Port-Harcourt teaching hospital (UPTH) with high grade fever of 1week duration, also developed joint pains, passage of coke colored urine, sensor neural deafness, hyperglycemia and petechial hemorrhage while on admission. Patient continued to have persistent fever despite having completed her anti-malaria and antibiotics, viral studies were subsequently done for her and she was found to have dengue virus. Patient was conservatively managed and discharged for follow-up in medical outpatient and Ear nose and throat clinic.